2017
DOI: 10.1002/2016ja023586
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of magnetic reconnection events and their associated auroral enhancements

Abstract: An analysis of simultaneous reconnection events in the near‐Earth magnetotail and enhancements in the aurora is undertaken. Exploiting magnetospheric data from the Geotail, Cluster, and Double Star missions, along with auroral images from the IMAGE and Polar missions, the relationship between a reconnection signature and its auroral counterpart is explored. In this study of 59 suitable reconnection events, we find that 43 demonstrate a clear coincidence of reconnection and auroral enhancement. The magnetic loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…However, the spatial ordering of both streamers and localized brightenings with respect to the flow channel is the same, suggesting that auroral brightenings are also associated with the upward FAC region on the duskward flank of the BBF. Other studies have shown similar correspondence and MLT offsets between auroral enhancements and fast flows or reconnection signatures in the magnetotail (Ieda et al 2001(Ieda et al , 2008Case et al 2017), but did not explicitly examine auroral streamers. These results may reflect an observation bias, with global auroral imagers unable to resolve the detail of narrow auroral streamers, particularly when the auroral oval is relatively narrow.…”
Section: Drivers/causesmentioning
confidence: 86%
“…However, the spatial ordering of both streamers and localized brightenings with respect to the flow channel is the same, suggesting that auroral brightenings are also associated with the upward FAC region on the duskward flank of the BBF. Other studies have shown similar correspondence and MLT offsets between auroral enhancements and fast flows or reconnection signatures in the magnetotail (Ieda et al 2001(Ieda et al , 2008Case et al 2017), but did not explicitly examine auroral streamers. These results may reflect an observation bias, with global auroral imagers unable to resolve the detail of narrow auroral streamers, particularly when the auroral oval is relatively narrow.…”
Section: Drivers/causesmentioning
confidence: 86%